Systemic lupus erythematosus and worsening severe preeclampsia: Does it have correlation? - Eva Febia; Cut M. Yeni (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Acute exacerbation of systemic lupus erythematosus in pregnancy complicated by severe preeclampsia was difficult to diagnose and treat. This is the case of Mrs Y, 26 years old in 24 weeks gestational age with severe preeclampsia with active exacerbation of systemic lupus erythematosus. She had suffered from systemic lupus eryhtematosus for three years before she got pregnant. When she came the blood pressure was 180/110 mmHg, protein urine +3. There was complaint of stiffness on muscle joints, facial flares, general weakness, and photosensitivity. She was hospitalized for seven days before she was discharged. Her blood pressure was controlled and lupus symptoms were controlled by antihypertensive agents and antiinflamation agent metil prednisolone. A week later she came back to our hospital. Her blood pressure was 190/110 mmHg despite having antihypertensive. She also complaint of joints ache, general weakness, facial flares, and no fetal movement. On ultrasound examination there was intra uterine fetal death. From this case, we would like to assess the patophysiology of systemic lupus erythematosus and worsening symptoms of severe preeclampsia which cause the mortality and morbidity of mother and baby